Artificial Intelligence, Cyberspace and International Law - Bhushan, Tripti (UI Scholars Hub, 2024)
Artificial Intelligence (AI) has become a significant technology that has transformed different sectors, including cyberspace. As AI continues to advance, it poses complex challenges to the existing international legal frameworks that govern cyberspace. This research paper examines the relationship between AI, cyberspace, and international law. It explores the impact of AI on the development of cyberspace and its potential consequences for international law. It also examines the existing international legal frameworks that regulate cyberspace and the challenges posed by the development of AI. This paper investigates the legal implications of AI and cyberspace on international law, specifically in the context of state responsibility and the laws of armed conflict. It discusses the challenges posed by the use of autonomous systems and the potential for their misuse, as well as the legal frameworks that govern their development, deployment, and use. Additionally, the paper examines the role of AI in the protection and promotion of human rights, including privacy and freedom of expression, and considers the AI’s potential as a tool for accountability and transparency in international law. Overall, the paper highlights the need for continued discussion and collaboration among stakeholders in order to ensure that the development and use of AI and cyberspace technologies are consistent with international legal norms and values. The paper concludes by providing recommendations on how international law can respond to the challenges posed by AI in cyberspace.